PENGARUH TIME BUDGET PRESSURE, AKUNTABILITAS, DAN PEMAHAMAN SISTEM INFORMASI TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA MEDAN - Susanti .; Wilsa Sitepu (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
The audit report presented must have good quality because it is the basis for decision making by economic actors. But in practice, many factors have led to a decrease in audit quality so that it has an impact on audit quality results. The objective of the study is to test and analyze the effect of time budget pressure, accountability, and understanding of information systems on audit quality. The research used a quantitative research method. The research populations were all auditors who worked on Public Accounting Offices in Medan City. The research data were collected by using questionnaires using a Likert scale. Based on the responses of respondents, it was concluded that partially, the time budget pressure did not have any significant effect on audit quality while accountability and understanding of partially information systems had a significant effect on audit quality in the Public Accounting Firm in Medan City. The result of determination coefficient was 66%. This indicated that the ability of audit quality variables can be explained by the variables of time budget pressure, accountability and understanding of information systems and the remaining 34% can be explained by other variables not examined such as objectivity, independence, auditor ethics, etc.